THE INFLUENCE OF SOCIOLOGICAL FACTORS, PARTY ID, EXPECTATION CONFLICT, AND CHECK AND BALANCES ON SPLIT TICKET VOTING BEHAVIOR IN BALI IN THE 2024 ELECTION - Pratista, Komang Putri Ganeesha (Reflektika, 2025)
The 2024 Indonesian general election, held on February 14, 2024, featured significant political shifts, particularly in the province of Bali. Historically, Bali has been a stronghold for the Indonesian Democratic Party of Struggle (PDI-P), which has consistently supported its candidates in legislative and presidential elections since the introduction of direct elections in 2004. However, a surprising change emerged in 2024: although the PDI-P remained dominant in the legislative elections, its presidential candidate lost to the Prabowo-Gibran ticket. This study analyzes the factors behind voters' split-ticket voting behavior, which deviates from the usual voting patterns in Bali. Using four theoretical frameworks sociological theory, party identification (non-rational approach), expectation conflict, and checks and balances (rational approach) this research employs quantitative methods and logistic regression analysis with the backward Wald method to assess voter behavior. The findings indicate that sociological variables, particularly place of residence, education level, and gender, along with party identification, significantly influence split ticket voting. On the other hand, rational choice theory does not show a significant effect. These results indicate that non-rational factors remain more influential in shaping electoral decisions in Bali, challenging the application of rational choice theory in the Indonesian electoral context. This study suggests the need for alternative or expanded theoretical models to better capture the complexity of voter behavior in future Indonesian elections.